2019
DOI: 10.1039/c9ra05987c
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of acetaminophen and 4-aminophenol with an electrochemical sensor based on silver–palladium bimetal nanoparticles and reduced graphene oxide

Abstract: Simultaneous detection of acetaminophen and 4-aminophenol with a highly sensitive electrochemical sensor based on silver–palladium bimetal nanoparticles and reduced graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Recently, various type of carbon based nanomaterials, such as single or multiwalled carbon nanotubes (SWCNT or MWCNT) [110], carbon nanostructures, graphene [111], Graphene 35 oxide [112], and reduced graphene oxide [113] have been synthesized, gaining attention due to their physical, optical, magnetic, and super electronic properties; these make carbon suitable for wide applications such as sensing devices [114], energy storage [115], and drug delivery [116].…”
Section: Carbon Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various type of carbon based nanomaterials, such as single or multiwalled carbon nanotubes (SWCNT or MWCNT) [110], carbon nanostructures, graphene [111], Graphene 35 oxide [112], and reduced graphene oxide [113] have been synthesized, gaining attention due to their physical, optical, magnetic, and super electronic properties; these make carbon suitable for wide applications such as sensing devices [114], energy storage [115], and drug delivery [116].…”
Section: Carbon Materialsmentioning
confidence: 99%
“…Carbon, one of the most versatile elements found on Earth, has attracted a lot of attention due to its special types of hybridization state (sp, sp 2 and sp 3 ), which make it capable of forming a wide range of allotropes from diamond (the hardest material) to graphite (the softest material). 108,109 Recently, various types of carbon based nanomaterial, such as single or multiwalled carbon nanotubes (SWCNTs or MWCNTs, respectively), 110 carbon nanostructures, graphene, 111 graphene oxide, 112 and reduced graphene oxide, 113 have been synthesized, which have gained attention due to their physical, optical, magnetic, and super electronic properties; these make carbon suitable for wide applications in sensing devices, 114 energy storage, 115 and drug delivery. 116 Various studies have confirmed the use of carbon-based materials for the detection of acetaminophen.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…The AgNPs-CB-PEDOT:PSS/GCE sensor showed good stability, reproducibility, and repeatability, and no interference occurred in the electrochemical detection of the analyte in the presence of glucose, caffeine, and urea molecules. rGO decorated with a suspension of Ag-Pd bimetallic nanoparticles (1 mg mL −1 ) and 1% chitosan solution (CS) was dropped onto the GCE surface to fabricate a voltametric sensor for the determination of acetaminophen [ 164 ]. The CS/Ag-Pd@rGO/GCE sensor showed high stability (96.3% of the initial value after 20 days storage at 4 °C) and good selectivity (1000-fold concentration of NaCl, KCl, CuSO 4 , and CaCl 2 did not affect the paracetamol determination).…”
Section: Application Of Silver Nanoparticles In Voltammetric and Ampe...mentioning
confidence: 99%
“…The aim of work is to present a time saving with simple steps procedure with considerable accuracy and sensitivity that can be applied successfully on real biological samples to have an advantage over already published methods dealing with electrochemical determination of APAP using RGO as they include multi-step and complicated working electrode preparation procedures requiring up to 4 h and limited to spiked samples only [27][28][29][30][31]. Initial SWV measurements were performed in a test solution of 100 μmol L −1 APAP in AcB (pH 5.0) with a series of electrodes, namely, the bare glassy carbon electrode (GCE, a commercial product by Metrohm), bare glassy-carbon paste electrode and its two modified variants: either with multi-walled carbon nanotubes (GCPE and MWCNT/GCPE, resp.…”
Section: Electrochemical Behaviour Of Acetaminophenmentioning
confidence: 99%